Магнітні нанокомпозити Fe3O4/SiO2 та імуносорбенти на їх основі - Semko, L. S.; Storozhuk, L. P.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
We prepared models of immunosorbents on the base of magnetite modified with silica (using tetramethoxysilane, tetraethoxysilane and sodium silicate as the precursores) carrying immobilized human Ig. It was estimated ability of the nanocomposites containing 0.1 – 0.7 g SiO2 (per 1 g magnetite) to adsorb Ig at varying concentrations. It was found that the maximal adsorbed amount of Ig for physical adsorption onto the nanocomposite containing 0.1 – 0.2 g SiO2 (per 1 g magnetite) is equal to 31 – 35 mg per 1 g nanocomposite.